796. Burden of Healthcare-associated (HA) Respiratory Syncytial Virus (RSV) in Hospitalized Adults. (4th December 2021) - Hill-Ricciuti, Alexandra C; Walsh, Edward E; Greendyke, William G; Barrett, Angela; Alba, Luis; Branche, Angela; Falsey, Ann; Phillips, Matthew R; Choi, Yoonyoung; Finelli, Lyn; Saiman, Lisa
Abstract: Background: Little is known about the burden of HA-RSV in hospitalized adults. We assessed risk factors and clinical outcomes in hospitalized adults diagnosed with HA-RSV. Methods: A retrospective case-control study was performed from 2017-2020 in two academic hospital systems. HA-RSV cases were >18 years of age, hospitalized >4 days, and developed new or worsening respiratory signs and symptoms that prompted clinicians to test for respiratory pathogens; cases were RSV-positive by PCR assays. Two community-onset (CO) RSV-positive controls (admitted with >2 acute respiratory symptoms), were matched to each HA-RSV case by age, sex, and RSV season. We compared risk factors and outcomes in cases vs. controls. We assessed escalation of respiratory support in HA-RSV cases, defined as new or increased respiratory support from Day -2 to Day +4 of their RSV-positive test. Exact conditional logistic regression compared outcomes of HA-RSV vs. CO-RSV subjects, adjusting for demographic and clinical characteristics. Results: 84 cases and 160 controls (both median 64 years) were included; 87% had ≥ 1 comorbidity. HA-RSV cases were hospitalized for a median of 10 (IQR: 5-17) days prior to their RSV-positive test. CO-RSV controls were more likely to have pulmonary comorbidities than HA-RSV cases (46% vs. 31%, p=0.02). 38% of HA-RSV vs. 15% of CO-RSV subjects were hospitalized ≥ 15 days after their RSV-positive test (p=0.047). 14% of HA-RSV and 6% of CO-RSV subjects died (p=0.25). Among patients who survived, HA-RSV cases were more likely discharged to a skilled nursing or rehabilitation facility than CO-RSV controls (46% vs. 17%, p=0.04). Of the 44 HA-RSV cases assessed thus far, 25% required escalation of respiratory support; none required initiation of mechanical ventilation. Conclusion: HA-RSV was associated with increased morbidity and increased health care resource use during and after hospitalization. RSV vaccines could prevent CO- and HA-RSV infections in adults. Disclosures: Edward E. Walsh, MD, GSK (Advisor or Review Panel member)Janssen (Grant/Research Support)Merck (Grant/Research Support)Merck (Grant/Research Support) William G. Greendyke, MD, Merck (Grant/Research Support) Angela Branche, MD, Merck Dohme and Sharpe (Grant/Research Support) Ann Falsey, MD, BioFire Diagnostics (Grant/Research Support)Janssen (Grant/Research Support)Merck (Grant/Research Support)Novavax (Other Financial or Material Support, DSMB member)Pfizer (Grant/Research Support) Matthew R. Phillips, MPH, Merck & Co., Inc. (Employee, Shareholder) Yoonyoung Choi, PhD, MS, RPh, Merck (Employee) Lyn Finelli, DrPH, MS, Merck (Employee) Lisa Saiman, MD, MPH, Merck (Grant/Research Support, Research Grant or Support)Merk Co., Inc (Grant/Research Support, Advisor or Review Panel member)